Comparing Jaffe and Enzymatic Methods for Creatinine Measurement at Various Icterus Levels and Their Impacts on Liver Transplant Allocation - Neda Soleimani; Sima Dehghani; Mohammad Hossein Anbardar; Sahand Mohammadzadeh; Elaheh Amirinezhad Fard; Atefeh Zare Sheibani; Mohammad Javad Esmaeili; Marsa Ebrahimi (International Journal of Analytical Chemistry)
The Model for End-Stage Liver Disease (MELD) scoring system is used to prioritize liver transplantations and assess disease severity. This includes the international normalized ratio (INR), creatinine, and total bilirubin. Since there are several ways to measure creatinine, MELD scores can produce inconsistent results. The objectives of this study were to define a valid cut-off for bilirubin interference in creatinine measurement and to assess the effects of various icteric levels on creatinine measurement and liver transplant allocation. A total of 400 serum samples were categorized into four groups based on their icteric indices and total bilirubin levels, including non-, mild, moderate, and severe icteric samples. Both chemical Jaffe and enzymatic techniques were used to determine the creatinine levels in all four groups, and the findings were compared. In parallel, serum samples from 83 liver transplant candidate patients were divided into three groups depending on their bilirubin levels and then similarly evaluated and interpreted. The MELD scores were then computed for each group and compared. In icteric samples, the enzymatic method produced higher results for the creatinine concentrations than the Jaffe method did, and the mean creatinine difference rose from 0.08 in nonicteric group to 1.95 in groups with severe icterus. In addition, the enzymatic approach yielded higher findings for creatinine and subsequently for MELD scores in patients who were liver transplant candidates. When the bilirubin concentration was above the 4 mg/dL threshold, there were differences between the approaches for both the creatinine and the MELD score (p values: 0.0001 and 0.027, respectively). The chemical Jaffe is a readily available and considerably cost-effective method for measuring creatinine. However, it is influenced by a variety of known and unknown interfering substances, and it should be applied cautiously when working with icteric samples. Alternate techniques such as the enzymatic method should be considered when the bilirubin level exceeds 4 mg/dL. Though this cut-off is instrument and kit-dependent, each laboratory is advised to have its cut-off for bilirubin interference.